The End of Professional Snobbery - Neil Seeman (Insights, 1999)
Imagine if no prestige attached to professions. Nobody cared about old-world credentials... MD, PhD, JD, MBA, MPH, MHsC: the letters would mean nothing, zip, in this alternate world.